Provider-recipient perspectives on how social support and social identities influence adaptation to psychological stress in sport - Hartley, Chris; Coffee, Pete; Abhyankar, Purva (Frontiers in Psychology, 2022)
Psychological stress can be both a help and a hindrance to wellbeing and performance in sport. The provision and receipt of social support is a key resource for managing adaptations to stress. However, extant literature in this area is largely limited to the recipient’s perspective of social support. Furthermore, social support is not always effective, with evidence suggesting it can contribute to positive, negative, and indifferent adaptations to stress. As such, we do not know how social support influences adaptations to stress in sport. The social identity approach may explain how social support can lead to both positive and negative adaptations to stress. Our purpose in this study was to explore how social support and social identities influence adaptations to stress in a Rugby Academy programme. Using qualitative methods within a naturalistic research paradigm, semi-structured interviews were conducted with Rugby Academy co-ordinators (n = 6) and players (n = 12), and four focus groups were conducted with teams of support staff (n = 18). Data were analysed using reflexive thematic analysis, which generated seven sub-themes categorised into two higher-order analytical themes. Our results demonstrate that group-based perceptions of social support influence adaptations to stress. Specifically, whether social support influences positive, negative, or indifferent adaptations to stress depended on (1) social factors influencing the nature of social support, and (2) social factors influencing the provision and receipt of social support. These findings advance our understanding of how adaptations to stress are influenced by social support. Implications are offered for how organisations, teams, and practitioners can facilitate positive adaptations to stress in sport.